Conceptual Foundations Of Effective Management In Higher Education Organizations - Levakov Izzatulla Nematillaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article explores the conceptual foundations of effective management in higher education organizations. In addition, the author's approach to the concepts of management and the organizational-economic mechanism of management systems, based on the results of the analysis of the problems observed in the field, features that need to be taken into account in the process of improving the management system of higher educational institutions, main tendencies and trends.